A novel molecular signature identifies mixed subtypes in renal cell carcinoma with poor prognosis and independent response to immunotherapy - Buettner, Florian A.; Winter, Stefan; Stuehler, Viktoria; Rausch, Steffen; Hennenlotter, Joerg; Füssel, Susanne; Zastrow, Stefan; Meinhardt, Matthias; Toma, Marieta; Jeronimo, Carmen; Henrique, Rui; Miranda-Goncalves, Vera; et al. (Genome Medicine, 2022)
Background: Renal cell carcinoma (RCC) is a heterogeneous disease comprising histologically defined subtypes. For therapy selection, precise subtype identification and individualized prognosis are mandatory, but currently limited. Our aim was to refine subtyping and outcome prediction across main subtypes, assuming that a tumor is composed of molecular features present in distinct pathological subtypes.
CRIS-Team WoS Importer:2022-09-23